PENGARUH SISTEM PENGENDALIAN INTERN, PENGELOLAAN KEUANGAN DAERAH, KOMITMEN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP PENERAPAN GOOD GOVERNANCE (Studi Kasus Pada Satuan Kerja Perangkat Daerah Kota Solok) - FANDRA YOVANO SYAFRION; Zirman Zirman; Azhari Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect of the intern control system, local financial management, organization commitment and organization culture on the implementation of good governance of local government in Solok City. It was a quantitative research utilizing a primary data which were obtained from questionnaire. The population of the study involved all units of local devices found in Solok City. The selection of the sample used purposive sampling methods with the characteristics of employees who perform the function of accounting / financial administrators, power users budget and budget users. There were about 100 respondents selected as the samples of the study, consisting of Chief SKPD, Secretary, Head of finance or the Head of administration and finance staff in each SKPD Solok City. The data were analyzed by using a multiple regression. The results of this study found that the intern control system, local financial management, organization commitment and organization culture has positive significant effect on the implementation of good governance with significant < 0.05.Keywords: good governance, intern control, financial management, organization commitment, organization culture